DNA barcoding herbaceous and woody plant species at a subalpine forest dynamics plot in Southwest China - Tan, Shao‐Lin (Ecol Evol, 2018)
Although DNA barcoding has been widely used to identify plant species composition in temperate and tropical ecosystems, relatively few studies have used DNA barcodes to document both herbaceous and woody components of forest plot. A total of 201 species (72 woody species and 129 herbaceous species) representing 135 genera distributed across 64 families of seed plants were collected in a 25 ha CForBio subalpine forest dynamics plot. In total, 491 specimens were screened for three DNA regions of the chloroplast genome (rbcL, matK, and trnH‐psbA) as well as the internal transcribed spacers (ITS) of nuclear ribosomal DNA. We quantified species resolution for each barcode separately or in combination using a ML tree‐based method. Amplification and sequencing success were highest for rbcL, followed by trnH‐psbA, which performed better than ITS and matK. The rbcL + ITS barcode had slightly higher species resolution rates (88.60%) compared with rbcL + matK (86.60%) and rbcL + trnH‐psbA (86.01%). The addition of trnH‐psbA or ITS to the rbcL + matK barcode only marginally increased species resolution rates, although in combination the four barcodes had the highest discriminatory power (90.21%). The situations where DNA barcodes did not discriminate among species were typically associated with higher numbers of co‐occurring con‐generic species. In addition, herbaceous species were much better resolved than woody species. Our study represents one of the first applications of DNA barcodes in a subalpine forest dynamics plot and contributes to our understanding of patterns of genetic divergence among woody and herbaceous plant species.